Failure analysis of work rolls of a thin hot strip mill. (April 2015) - Palit, Piyas; Jugade, Hrishikesh R.; Jha, Arvind Kumar; Das, Souvik; Mukhopadhyay, Goutam
Highlights: In hot rolling mills, premature failure of rolls is a major concern. This work describes two different types of roll failure. Case I: enhanced ICDP Bottom roll of fifth stand (F#5) which failed from the neck portion. Case II: analysis of sub-surface defect of ICDP rolls of the last stand (F#6). It has been cleared from the article that the roll manufacturing plays a significant role in performance of roll. Abstract: In hot rolling mills, premature failure of rolls is a major concern as it adversely affects the mill operation as well as production. Analysis of failed roll materials and actual rolling conditions in service are therefore necessary to understand the roll failure mechanism and thereby improve the wear resistance and extend the service life of rolls. The hot strip mill referred here consists of six stands wherein high chromium (Hi-Cr) iron rolls and Indefinite Chilled Double Poured (ICDP) cast iron rolls are being used for finishing rolling of the strips in the last two stands. The thin strip mill produces strips in the thickness range of 1.0–12.7 mm. This work describes two different types of roll failure cases and their analysis which was carried out using destructive as well as non-destructive testing techniques (NDT). The cases are as follows: (a) Case I: enhanced ICDP bottom roll of fifth stand (F#5) which failed from the neck portion. (b) Case II: analysis of sub-surface defect of ICDP rolls of the last stand (F#6). Destructive testing (including metallography and chemical analysis) was carried out on the failed roll samples in the first case and gross abnormality in microstructure was observed. Some foreign particle/entrapment was observed after dressing of the working surface of roll at 566 mm diameter (initial diameter of roll was 620 mm and scrap diameter was projected to be 540 mm). The chemical composition of the particle was analyzed by a portable X-Ray Fluorescence (XRF) alloy analyzer and it was confirmed that the particle is basically a ferroalloy which was entrapped in the shell of the roll, probably during casting/manufacturing of roll.